Impact of history of periodontitis on gene expression of bone-related factors in young patients - Fabiano Ribeiro CIRANO; Suzana Peres PIMENTEL; Fernanda Vieira RIBEIRO; Marcio Zaffalon CASATI; Renato Corrêa CASARIN; Daniel Freire GALLAFASSI; Denise NISHII; Mônica Grazieli CORRÊA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Although dental implants and bone regenerative procedures are important approaches for the reestablishment of esthetics and function in young patients with a history of generalized aggressive periodontitis (GAP), no predictable outcomes have been reported, and the host osteo-immunoinflammatory response may play a relevant role in this context. In view of the lack of molecular investigations into the bone tissue condition of young patients with periodontitis, the aim of this study was to evaluate the gene expression of bone-related factors in this population. Bone biopsies were obtained from the posterior mandible in 16 individuals previously diagnosed with GAP and on periodontal support therapy and from 17 periodontally healthy (PH) patients. The gene expression of tumor necrosis factor (TNF)-α, transforming growth factor (TGF)-β, receptor activator of the NF-κB ligand (RANKL), osteoprotegerin (OPG), osteocalcin (OC), bone sialoprotein (BSP), and type I collagen (COL-I), important biomarkers of bone turnover, was evaluated by qRT-PCR. Lower TGF-β and OPG mRNA levels were observed in GAP patients compared to PH individuals (p ≤ 0.05). There were no between-group differences in levels of TNF-α, BSP, RANKL, OC, or COL-I mRNA (p>0.05). In young adults, a history of periodontal disease can negatively modulate the gene expression of important bone-related factors in alveolar bone tissue. These molecular outcomes may contribute to the future development of therapeutic approaches to benefit bone healing in young patients with history of periodontitis via modulation of osteo-immuno-inflammatory biomarkers.